Overview of research and applications of new generation information technologies in intelligent mines - JIANG He; CHENG Deqiang; YI Fudi; WANG Peng; CUI Wen; KOU Qiqi (Gong-kuang zidonghua)
With the rapid development of information technology and the increasing demand for the intelligent transformation and upgrading of mining operations, the exploration and application of new generation information technologies in the field of intelligent mining have continued to deepen. This paper briefly describes the theoretical system of mine informatization, digitization, and intelligence, which covers the entire process from data collection and processing to intelligent decision-making, laying the foundation for the transformation and upgrading of mines. It reviews the core technologies, typical application scenarios, and future development trends of intelligent mine monitoring and control technologies, big data intelligent analysis and decision-making technologies, predictive maintenance technologies for mining equipment, industrial IoT technologies in intelligent mines, AI technologies in intelligent mining, digital twin technologies in mining, robotics in mining, and 5G communication technologies in mining. The core components of intelligent mine monitoring and control technology are high-precision sensor networks, the Internet of Things (IoT), big data analysis, and AI. Key technologies in big data intelligent analysis and decision-making for mines include data collection and integration, intelligent data analysis, and decision support. Predictive maintenance technologies for mining equipment mainly involve data collection, data analysis, fault diagnosis, and maintenance decision optimization. Industrial IoT technologies in intelligent mines span from the sensing layer to the application layer, achieving efficient and intelligent mine safety management. AI technologies in intelligent mines hold great application potential in predictive maintenance, self-optimization, human-machine collaboration, and automated control. The core of digital twin technology in mining includes IoT, 3D visualization and modeling, AI and machine learning, and high-reliability communication technologies. Robotics technology in mining is widely applied in fields such as autonomous driving, intelligent mining, environmental sensing and monitoring, and multi-robot collaborative operations. The core advantages of 5G technology in mining are high speed, low latency, large connection density, high reliability, and stability, which are applied in fields like multi-sensor fusion monitoring, autonomous driving, 5G edge computing, and virtual reality/augmented display.